Breastfeeding experiences and women's self-concept: Negotiations and dilemmas in the transition to motherhood - Augusto, Amélia; Neves, Dulce Morgado; Henriques, Vera (Frontiers in Sociology, 2023)
Breastfeeding is much more than a biological event. It is a social construction, full of cultural meanings and framed by social structures. Being, simultaneously, a natural event and a social practice, breastfeeding poses challenges to feminist approaches in the sense it may be acknowledged as an empowering practice for women and/or as a setback in the process of women's social emancipation, condemning them to the domestic sphere and to traditional gender roles. Often focused on the product, i.e. the milk and its beneficial properties for the infant’s health, the dominant discourse on breastfeeding makes it a trait of good mothering, withdrawing the understanding of the particular (but also structural) contexts in which this practice occurs. Using first-person testimonies, from first child mothers, about transitions to motherhood, this paper aims to identity features of prevailing breastfeeding regimes in the Portuguese society and to capture challenges brought by breastfeeding and other embodied practices of motherhood, exploring the lived experiences, the difficulties and dilemmas, the impacts of social expectations and judgements, the work-family balance, as well as the negotiation processes taking place within couples and early-parents. Despite being subject to tensions and sometimes stressful adaptation processes, motherhood and breastfeeding tend to be ultimately described by women as experiences that enhance welcome changes in personal trajectories, life priorities and identities.